Aplikasi Pemetaan Rumah Kos Disekitar Ums Berbasis Google Map Api - Muttaqien, Gema Ilham, Prof. Dr. Budi Murtiyasa, M.Kom, Dedi Gunawan, S.T. , MSC (2016)
In common cases, students, especially for new students, are looking for a dorm using a conventional techniques, such as: asking to friends, dorm biro, or even to the dorm's owner directly. When they ask to those people, generally they ask about dorm's facilities, monthly or yearly dorm's rent cost, and the distance between the dorm to the university. The system built will use Google Map API Java Script as mapping application. In addition, PHP programming language and MySQL database will be added to store the detail data and the location. This application can be accessed by using browser in both computer and smartphone. By the existence of mapping application using Google Map API helps students to decide which dorm that they will choose. This mapping application is equipped with pictures and detail data of the dorm, so that it will support students's decision.